A computational fluid dynamics study of combustion and emission performance in an annular combustor of a jet engine - Zuber, Mohammad; Badrul Hisham, Muhammad Syafiq; Mohd Nasir, Nur Athirah; Basri, Adi Azriff; Khader, S. M. Abdul (Universiti Putra Malaysia Press, 2017)
This paper is a Computational Fluid Dynamics (CFD) study of the performance of a jet engine annular combustor that was subjected to various loading conditions. The aim is to comprehend the effect of various genuine working conditions on ignition and emission performance. The numerical models utilized for fuel ignition is the feasible k-ω model for turbulent stream, species transport (aviation fuel and air) with eddy-dissipation reaction modelling and pollution model for nitrogen oxides (NOX) emission. The results obtained confirm the findings described in the literature.